The Impact of Digital Taxation on the Creative Economy and E-Commerce in Indonesia - Rizka Novelia; Claudya Nurcahaya; Billy Dewantara (Journal of Innovative and Creativity, 2025)
This article review explores the impact of digital taxation on the growth and sustainability of the creative economy and e-commerce sectors in Indonesia. As the digital landscape expands rapidly, the implementation of taxes on digital transactions has emerged as both an opportunity and a challenge. On one hand, digital taxation provides a new revenue stream for the government and ensures fair competition between domestic and foreign digital service providers. On the other hand, it raises concerns among small and medium-sized enterprises (SMEs) and creative entrepreneurs about increased operational costs, reduced competitiveness, and potential barriers to market entry. The review synthesizes insights from recent studies (2020–2025) on the economic, regulatory, and technological dimensions of digital taxation, highlighting its implications for innovation, consumer behavior, and cross-border e-commerce. The findings suggest that while digital taxation can promote fiscal sustainability and equitable market practices, its design and enforcement must balance revenue needs with the goal of fostering innovation and inclusivity in Indonesia’s vibrant digital economy.